Hadith #4456 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; Habib bin Salm al-Ansari حبيب بن سالم الأنصاري مولى; Khalid bin Arfth خالد بن عرفطة; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Qatada قتادة (Sunan Abi Dawud)
while I was wandering in search of my camels which had strayed, a caravan or some horsemen carrying a standard came forward. The bedouin began to go round me for my position with the Prophet (ﷺ). They came to a domed structure, took out a man from it, and struck his neck. I asked about him. They told me that he had married his father’s wife.
Grade: Sahih

Hadith #4457 - Sunan Abi Dawud - al-Nu'man bin Bashir ibn Sa'd; Habib bin Salm al-Ansari حبيب بن سالم الأنصاري مولى; Ja'far bin Iyas; Khalid bin Arfth خالد بن عرفطة; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
I met my uncle who was carrying a standard. I asked him: Where are you going? He said: The Messenger of Allah (ﷺ) has sent me to a man who has married his father’s wife. He has ordered me to cut off his head and take his property.
Grade: Sahih